Feeding the Nineteenth-Century Baby: Implications for Museum Collections - Nowell-Smith, Felicity (Material Culture Review, 1985)
This paper discusses the implications inherent in different methods of infant feeding in the Western world c. 1700-1900, within the context of the historiography of the last ten years. A n account of how infants were fed in the nineteenth century is interwoven with the evidence for what occurred in Ontario. This evidence is both archival and artifactual. The objects discussed and illustrated are in the collections of the Museum of the History of Medicine in Toronto. Artifactual evidence of infant feeding practices is particularly vulnerable. Objects made of glass break easily, and infancy itself lasts only a short time. At best, the objects once abandoned are hard to recognize and therefore ignored. An examination of the artifacts suggests their manner of use and possible difficulties, problems, or advantages associated wit h them. These observations can be used to test hypotheses about implications of infant feeding practices based solely on archival evidence. Résumé Dans le cadre de l'historiographie des dix dernières années, ce document tire des conclusions sur les différentes méthodes d'alimentation des nourrissons en Occident pour la période couvrant les années 1700 à 1900. Une histoire de ces méthodes d'alimentation doit nécessairement utiliser des sources de documentation ontariennes, à savoir des archives et des témoins matériels. Les objets étudiés et illustrés dans cette monographie proviennent du Museum of the History of Medicine à Toronto. Les témoins matériels de ces méthodes d'alimentation des nourrissons sont particulièrement fragiles: les objets de verre cassent facilement et la période de la petite enfance ne dure pas longtemps. Au mieux, on ne tient pas compte de ces objets qui, une fois laissés de côté, sont difficiles à identifier. Un examen de ces témoins matériels en révèle la méthode d'utilisation ainsi que les avantages, les problèmes et les difficultés probables qui leur sont liés. Ces observations peuvent servir à vérifier les hypothèses sur les conclusions à tirer des méthodes d'alimentation des nourrissons, hypothèses fondées exclusivement sur des documents d'archives.